DETERMINATION OF LANSOPRAZOLE IN CAPSULES USING METHODOLOGY BASED ON DIGITAL IMAGES. (REMUNOM, 2024)
In this work, it is proposed to determine the content of lansoprazole, a selective inhibitor of gastric H+/K+-ATPase, using titration based on digital image (Digital Image-Based Titration). The DIB system uses a webcam to acquire digital images based on the RGB (Red-Green-Blue) color system. During the titration procedure, the method was applied to the acid-base titration of the drug lansoprazole with hydrochloric acid. Titration was performed by DIB and potentiometry. In the DIB methodology, for each volume of titrant added, an image was captured and manipulated to obtain the norm values (N=√R̅2+G̅2+B̅2). The volume of titrant used to reach the equivalence point was obtained from the second derivative of the titration curve. The results obtained from the samples did not show any significant statistical difference at the 95% confidence level, which was verified after applying the paired t-test (tcalculated = 0.439 and tcritical = 2.353). The relative standard deviations using the DIB methodology, with the exception of sample C, were below 1.0%.